School-based disaster risk reduction education in primary schools in Da Nang City, Central Vietnam. (1st October 2016) - Thi, Tong; Shaw, Rajib
ABSTRACT: The concept of school-based disaster risk reduction (DRR) education has increasingly become popular as greater emphasis is placed on the role of schools in reducing risks and building the resilience of the education system. This paper discusses the variations in the implementation of DRR education among primary schools in different areas including urban, rural, mountainous, plain and coastal areas in Da Nang City, Central Vietnam. For rural schools, similarities in the implementation of DRR education are observed and schools in both rural plain and rural mountainous areas stress the provision of disaster-related training. In addition, improvement of school buildings and external relationship is important for the resilience of urban schools. Specifically, for schools in urban coastal areas, school location and structure are significant, while for schools in the urban plain lands, enhancement of collaboration with their community has the most potential to contribute to the resilience of a school. From that, this research proposes that leadership and prioritization are key factors in helping schools to manage internal and external resources to efficiently overcome challenges and effectively promote DRR education towards the enhancement of schools' resilience.